2022
DOI: 10.3390/s22031037
|View full text |Cite
|
Sign up to set email alerts
|

Use of Robotic Platforms as a Tool to Support STEM and Physical Education in Developed Countries: A Descriptive Analysis

Abstract: The lack of interest of children at school is one of the biggest problems that Mexican education faces. Two important factors causing this lack of interest are the predominant methodology used in Mexican schools and the technology as a barrier for attention. The methodology that institutions have followed has become an issue because of its very traditional approach, with the professor giving all the theoretical material to the students while they listen and memorize the contents, and, if we add the issue of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…Arduino-series Platform Arduino, Arduino C [14,15] FRDM-KL05Z, C [16] TCLab Arduino Kit, MATLAB or Python [17] Arduino, LabView and Scratch [18] LEGO-series Platform LEGO EV3, MATLAB [19,20] LEGO EV3, Block-based Programming [21] LEGO EV3, EV3-G [22] LEGO EV3, LabView [23] LEGO EV3, Scratch [24] LEGO WeDo, Scratch [25] A review of this literature can provide insight into teaching trends and some details of the courses. However, most works in the literature focus on the course content, and few focus on the design methods of robotics experiments and students' hands-on experimental results.…”
Section: Graphical Programming Languagementioning
confidence: 99%
“…Arduino-series Platform Arduino, Arduino C [14,15] FRDM-KL05Z, C [16] TCLab Arduino Kit, MATLAB or Python [17] Arduino, LabView and Scratch [18] LEGO-series Platform LEGO EV3, MATLAB [19,20] LEGO EV3, Block-based Programming [21] LEGO EV3, EV3-G [22] LEGO EV3, LabView [23] LEGO EV3, Scratch [24] LEGO WeDo, Scratch [25] A review of this literature can provide insight into teaching trends and some details of the courses. However, most works in the literature focus on the course content, and few focus on the design methods of robotics experiments and students' hands-on experimental results.…”
Section: Graphical Programming Languagementioning
confidence: 99%
“…Pembelajaran berbasis STEM dengan robotika dapat mengembangkan pengetahuan dan kesadaran robotika bagi siswa (Haerani & Erna, 2022;Lathifah et al, 2019). Selain itu, pelibatan siswa secara aktif dan interaktif dalam perakitan robot dapat menambah motivasi dan kemampuan berpikir siswa (Leonard et al, 2023;Ponce et al, 2022). STEM juga telah berdampak pada jalur karier siswa dan telah mengembangkan keterampilan analitisnya secara mendalam sehingga dapat meningkatkan minat dan motivasi belajar mereka (Alhakiki & Taufina, 2020;Lavi et al, 2021;Li et al, 2019).Salah satu inovasi di bidang teknologi yang menarik perhatian banyak orang adalah robot rover penjelajah Mars (Lathifah et al, 2019;Long et al, 2021).…”
Section: Pembahasanunclassified
“…Results showed that no significant difference was found in the students' learning attitude, programming skills, and learning engagement between VPR and PR. Ponce et al (2022) This work proposes the use of robotic platforms inside elementary schools and universities to improve and evaluate the usability and effectiveness of robots on students' attention spans, motivation, and knowledge acquirement during their classes.…”
Section: Alvarez-(2020)mentioning
confidence: 99%